Army-Navy Nurse Corps: hearings before the United States Senate Committee on Armed Services, Eightieth Congress, first session, on Mar. 24, 1947. - United States. (U.S. G.P.O., 1947)
Considers (80) H.R. 1943
Record is based on bibliographic data in CIS US Congressional Committee Hearings Index. Reuse except for individual research requires license from Congressional Information Service, Inc.
Indexed in CIS US Congressional Committee Hearings Index Part V
Considers (80) H.R. 1943